The Effectiveness of Counselling Using Animated Video on the Behaviour Regarding Dental Caries among Elementary School Students - Irmanita Wiradona; Fitri Ihsan Setyowati; Sadimin Sadimin; Wahyu Jati Dyah Utami; Yodong Yodong (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Health is an important concern among the community, including dental and oral health. Dental caries is a common problem in Indonesia that is often neglected by patients.Education on the importance of dental health through promotional media such as animated video is needed in order tochange community’s behaviour regarding this issue. This study examined the effect of counselling using animated video on elementary school students’ behaviour regarding dental caries issue. This quasi-experimental study employed one group pre-test post-test design, involving 56 students from third, fourth and fifth grades at SDN SrondolWetan 02 Banyumanik, Semarang City as population and samples. Data were analysed using t-test, which results indicated gaps in students’ knowledge, attitudes and actions regarding dental caries before and after counselling using animated video (p value: 0.000). It is concluded that counselling using animated video can improve the behaviour regarding dental caries among students of the third, fourth and fifth grades at SDN Srondol Wetan 02 Banyumanik, Semarang City.Keywords :counselling, animated video, behaviour